Transcendence and Sublime Experience in Nature: Awe and Inspiring Energy - Bethelmy, Lisbeth C.; Corraliza, José A. (Frontiers in Psychology, 2019)
The wilderness is one of the most widely recognized sources of transcendent emotion. Various recent studies have demonstrated nature’s power to induce intense emotions. The study at hand will generate conceptual and operational definitions of sublime emotion toward nature. Taking into consideration the recent research on feelings of awe, an instrument is devised to measure sublime emotion toward nature. The proposed scale’s reliability and validity is tested in a sample of 280 participants from the general population of Madrid. Results show that sublime emotion was defined by two conceptual components: awe, and inspiring energy, both obtained using the computer program FACTOR. After reliability and validity analysis, the Sublime Emotion toward Nature (SEN) scale included 18 items, distributed into awe (6 items, α = .881) and inspiring energy (12 items, α= .933). Awe was defined by feelings of fear, threat, vulnerability, fragility, and respect for nature, which is perceived as vast, powerful, and mysterious. Inspiring energy was defined by feelings of vitality, joy, energy, oneness, freedom, eternity, and harmony with the universe. The SEN is an adequate instrument to measure transcendent emotions provoked by direct wilderness exposure or memory thereof.